Efektivitas Pengembangan Instrumen Penilaian Autentik Berbasis Penguatan Pendidikan Karakter Untuk Siswa Kelas IV SD - Stela Ramadhani Khalashinikov; Murtono Murtono; Santoso Santoso (Universitas Negeri Makassar, 2020)
Research this aim to analyze and describe the effectiveness development instrument appraisal authentic attitude spiritual and attitude social-based strengthening education character (PPK) on student class IV primary school sub-district teak group ismoyo. Method research uses research and development (R & D) with model development according to Borg and Gall. Effectiveness instrument average thematic based strengthening education character (PPK) and be equipped with instrument appraisal authentic attitude spiritual and attitude social-based strengthening education character (PPK) proven effective. Result learn pretest class control and experiment, that is on class control 28,58 while on class experiment 30,14. After implemented test tries during the 6-time meeting, score average-average posttest on group control and experiment increased becomes 35,68 and 37,78. Result test t obtained score t count = 3,140 with level significance sig. (2-tailed) 0,002 < α = 0,05. Activity learns students' class control reach average 26% category enough well and class experiment reaches 54,6% average category well. Thereby, enhancement of the result learn students higher on group experiments. N Gain that obtained 0,27 that show numbers < 0,3 which means that very effective. The conclusion from the resulting research just now shows very effective.